Creación de una guía didáctica sobre la herramienta google web designer orientada a la creación de recursos didácticos basados en html5, css3 y javascript como alternativa adobe flash - Rengel Tillaguango, Luis Fernando (2014)
In the twenty-first century it is essential that Tic is incorporated into the teaching process, because the technologies have entered the homes and therefore should be present in the theoretical field. For this reason this work is part of the desire to introduce new tools in the PEA. The computer mediated education is the new event to teach students, and spent more and more open in the educational world, according to the technological age in which we live. The multimedia education has many tools for development, one of them are tutors and tutorial that will improve knowledge in the use of the Google Web Designer application, since it is a necessary tool for the development of teaching aids designed to education. Research techniques that contributed to the development of the following study aid served to achieve the related objectives such as observation, the survey allowed for direct interaction with the object of study, with applications of the methods: scientific, deductive and inductive methodology that allowed for the design and construction of the tutor (computerized-guide-). The relevant and essential topics to serve as effective support to achieve its guidance for use and the benefits of GWD application and conside as a valid alternative to the Flash tool.